Critical Thinking Assessment Profile of Biology Teacher Candidate Students of FTTE Tanjungpura University - Eka Adha Apriliani; Afandi Afandi; Anisyah Yuniarti (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2023)
Critical thinking is a skill needed in 21st century education. This research was carried out using a quantitative descriptive method. Before collecting data, the test questions were tested first to determine their validity and reliability using tools such as Microsoft Exel 2016 software and Iteman Version 3.0. In this study, it can be seen that the Critical Thinking Assessment profile of prospective biology teacher from biology education students at FTEE UNTANis mostly included in the critical category with an average value of 70.40.